Arthritis-associated osteoclastogenic macrophage, AtoM, as a key player in pathological bone erosion - Tomoya Agemura; Tetsuo Hasegawa; Shinya Yari; Junichi Kikuta; Masaru Ishii (BMC, 2022)
Abstract Osteoclasts are myeloid lineage cells with a unique bone-destroying ability that maintains bone homeostasis together with bone formation by osteoblasts. An advanced intravital imaging system using a two-photon microscopy has enabled the observation and evaluation of osteoclast dynamics and behaviors in the bone marrow of living mice. Using this system, it has become clear that pathological osteoclasts under inflamed conditions differ from physiological osteoclasts under a steady-state. Recently, we identified novel osteoclast precursors in arthritis, called arthritis-associated osteoclastogenic macrophages (AtoMs), which differentiate into pathological osteoclasts and induce inflammatory bone destruction. In this review, we introduce the in vivo imaging of physiological and pathological osteoclasts and their differentiation mechanism.